Neutrophil-to-lymphocyte ratio-based prognostic score can predict outcomes in patients with advanced non-small cell lung cancer treated with immunotherapy plus chemotherapy - Shan Liao; Huiying Sun; Hao Lu; Jiani Wu; Jianhua Wu; Zhe Wu; Jingle Xi; Wangjun Liao; Yuanyuan Wang (BMC Cancer)
Abstract Backgroud Immune checkpoint inhibitor (ICI) plus chemotherapy has become the standard of care for advanced non-small cell lung cancer (NSCLC). Nonetheless, reliable efficacy biomarkers of ICI plus chemotherapy are lacking. In this research, we sought to explore efficacy biomarkers and construct robust prognostic models in NSCLC patients treated with ICI plus chemotherapy. Methods We retrospectively analyzed 171 patients with advanced NSCLC treated with ICI plus chemotherapy. Clinical characteristics and peripheral blood inflammatory indexes were collected and prognostic models were constructed to explore efficacy and prognosis biomarkers of ICI plus chemotherapy. Results In the cohort that received first-line ICI plus chemotherapy, pre-treatment neutrophil-to-lymphocyte ratio (NLR) > 3.3 and fibrinogen (FIB) > 3.196 were associated with worse efficacy and were independent risk factors of progression-free survival (PFS). Compared to programmed cell death ligand 1 (PD-L1), the derived NLR-FIB (NF) score had significantly improved accuracy in predicting efficacy and prognosis. In advanced NSCLC patients with targetable oncogenic driver alterations receiving second- or post-line ICI plus chemotherapy, pre-treatment NLR > 3.53 was associated with worse efficacy and was an independent risk factor of PFS and OS; Tyrosine kinase inhibitor (TKI)-PFS > 12 months were independent risk factors of overall survival (OS). Secondary epidermal growth factor receptor (EGFR)-T790M mutation, platelet-to-lymphocyte ratio (PLR) > 196.81 and albumin (ALB) < 40.25 were associated with worse PFS. Based on NLR and TKI-PFS, an NLR-TKI-PFS (NTP) score was constructed with three OS risk prognosis categories: favorable, intermediate, and poor (corresponding to a median OS of 21, 12, and 5.3 months). Conclusions The noninvasive NF score, combining NLR > 3.3 and FIB > 3.196, was superior to PD-L1 estimated from tumor tissue in predicting the efficacy and prognosis of first-line ICI plus chemotherapy in advanced NSCLC patients. The noninvasive NTP score, combining NLR > 3.53 and TKI-PFS > 12 months, is a valuable tool for predicting OS and PFS in advanced NSCLC patients with targetable oncogenic driver alterations receiving second- or post-line ICI combination therapy.